2002
DOI: 10.1354/vp.39-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sublethal Microcystin-LR Exposure in Mice

Abstract: Microcystin-LR (MCLR) is a potent hepatotoxin produced by the cyanobacterium Microcystis aeruginosa. The histology of acute lethal toxicity has been well characterized, but histology is limited regarding sublethal exposure. Balb/C mice were given a single sublethal dose of MCLR (45 microg/kg) and euthanized at 2, 4, 12, and 24 hours after exposure. Centrilobular to midzonal hepatocellular hypertrophy with loss of cytosolic vacuolation consistent with glycogen depletion occurred at 2 hours. At 4 hours, central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 35 publications
5
42
0
4
Order By: Relevance
“…Liver levels of microcystin toxin are being determined. Typical hepatic necrosis seen in mammalian cases of algae microcystin toxicity 20 was not present in these crocodiles, although species differences in susceptibility and tissue responses to this toxin may occur. In addition, cyanobacteria produce a variety of toxins, the effects of some of which are not well characterized.…”
Section: Pathogenesismentioning
confidence: 86%
“…Liver levels of microcystin toxin are being determined. Typical hepatic necrosis seen in mammalian cases of algae microcystin toxicity 20 was not present in these crocodiles, although species differences in susceptibility and tissue responses to this toxin may occur. In addition, cyanobacteria produce a variety of toxins, the effects of some of which are not well characterized.…”
Section: Pathogenesismentioning
confidence: 86%
“…Alterations associated with chronic sublethal exposure to MCLR have also been characterized. Balb/c mice administered sublethal intraperitoneal (45 µg/kg/d) doses of MCLR for 4 or 7 days exhibited marked hepatocytomegaly and karyomegaly with numerous multinucleated cells (Guzman and Solter, 2002). In rats, prolonged sublethal (16, 32, and 48 µg/kg/day) exposure to MCLR for 28 days was found to have multiple dose-dependent hepatotoxic effects including increased hepatic apoptosis, steatosis and centrilobular fibrosis (Solter et al, 1998).…”
Section: Microcystin-lr (Mclr) Is Cyclic Heptapeptide Produced By Thementioning
confidence: 99%
“…The high selectivity to liver is believed to be due to toxin uptake via bile acid carriers (Suchy, 1993;Sahin et al, 1996). Histopathological studies in both fish and mammals revealed serious lesions of the liver including rounding and separation of hepatocytes, disruption of hepatic cords, hepatocyte necrosis and degeneration, and severe intrahepatic hemorrhage leading to lethal hypolovemic shock or liver failure (Guzman and Solter, 2002;Li et al, 2003Li et al, , 2004Malbrouck et al, 2003;Handeland and Ostensvik, 2010).…”
Section: Introductionmentioning
confidence: 99%